Interconnections and continuity among planning documents of Kota Lama Semarang development within the context of urban heritage conservation - Kartikasari, Anisa Nurul (Emerland, 2022)
Purpose – Urban conservation is an integral part of urban development planning and it is incorporated into land use rules and plans. In order to achieve the goals of an ideal heritage conservation policy, there are spatial plans, building codes and relevant regulations that should be well prepared as reference for development projects. Kota Lama Semarang (Old City of Semarang) area has been recognized as part of the origin of the development of Semarang City, the capital city of Central Java. This area has been designated as a cultural heritage area both at the city and national level since 2020. The Heritage City Conservation Program (P3KP) encourages Kota Lama Semarang Area to experience fairly massive development since 2013. On one hand, to control and manage the area, the Semarang City Government issued several official planning documents, i.e. (a) Kota Lama Semarang Area RTBL documents (2003); (b) Kota Lama Semarang Grand Design (2011); and (c) Kota Lama Semarang Site RTBL (2020), which consecutively were used as references of development projects. On the other hand, the results of development projects indicated that there are no coherent physical improvements in the area. The study was conducted to show whether there are consistencies or mismatches between the three planning documents. Design/methodology/approach – This study used a qualitative deductive method with content analysis technique to compare three planning documents, using the predetermined variables. Findings – The results showed that the consistency between the three planning documents was not fully demonstrated, but they are mutually interconnected. Research limitations/implications – The research focused only on three formal planning documents, for which comparative analysis was undertaken using content analysis to identify consistencies and inconsistencies based on determined 9 variables. Practical implications – Good planning documents should be consistent, since they are used as development references. Inconsistencies among planning documents produced segmented urban environments in Kota Lama Semarang Area/Site, which are mostly due to the different institutions preparing the documents. Social implications – The segmented urban development in the area has reduced the historical and cultural values of the area. Revitalization program that was undertaken has some implication to the sustainability of the local economy. Originality/value – The paper explores both the consistencies and mismatches among the three planning documents, which have been used as references in implementing development projects in Kota Lama Semarang Area. Failures in maintaining consistencies among documents are supposed to produce inconsistent physical development in the area, unless adjustment to current development has to be made.